2000
DOI: 10.1007/s004280000241
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonia in Hermansky-Pudlak syndrome: significance of florid foamy swelling/degeneration (giant lamellar body degeneration) of type-2 pneumocytes

Abstract: Although usual interstitial pneumonia (UIP)-like IP has been known as the most serious complication of Hermansky-Pudlak syndrome (HPS), its pathologic features and pathogenesis are poorly understood. We investigated biopsied and autopsied lung tissues from five patients who died of UIP-like IP associated with HPS (HPSIP). The salient histopathologic features of HPSIP observed were: (1) alveolar septa displaying florid proliferation of type-2 pneumocytes (2PCs) with characteristic foamy swelling/degeneration; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 29 publications
11
115
0
2
Order By: Relevance
“…Interestingly, mutations in the surfactant SP-C gene are associated with familial desquamative and nonspecific interstitial pneumonitis in children and UIP in adults. A similar defect in surfactant processing and secretion appears to result in "giant lamellar body degeneration" of type II AECs observed in the HermanskyPudlak syndrome, which is associated with mutations in the Hermansky-Pudlak syndrome-1 gene and interstitial pneumonia (43). The potential role of defects in protein processing and trafficking in sporadic cases of IIPs is unknown; these observations, nonetheless, reinforce the importance of gene-environment interactions in the expression of varied host tissue reactions and phenotypes.…”
Section: What Are the Cellular And Molecular Mechanisms For Injury/apmentioning
confidence: 83%
“…Interestingly, mutations in the surfactant SP-C gene are associated with familial desquamative and nonspecific interstitial pneumonitis in children and UIP in adults. A similar defect in surfactant processing and secretion appears to result in "giant lamellar body degeneration" of type II AECs observed in the HermanskyPudlak syndrome, which is associated with mutations in the Hermansky-Pudlak syndrome-1 gene and interstitial pneumonia (43). The potential role of defects in protein processing and trafficking in sporadic cases of IIPs is unknown; these observations, nonetheless, reinforce the importance of gene-environment interactions in the expression of varied host tissue reactions and phenotypes.…”
Section: What Are the Cellular And Molecular Mechanisms For Injury/apmentioning
confidence: 83%
“…Pulmonary findings commonly described in adults with HPS from case series and case reports include macrophage-predominant inflammation, ceroid deposits within macrophages, and progressive honeycombing on highresolution computed tomography indicative of progressive pulmonary fibrosis (3,33,34). Longitudinal studies establishing the natural history of HPS lung disease are limited and have included only adults after presentation with restrictive lung remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The surfactant-containing lamellar body exhibits an acidic pH, undergoes regulated secretion, and possesses lysosomal transmembrane proteins in the limiting membrane, notably Lamp1 and Lamp3. Autopsy studies of adults with HPS have demonstrated foamy degeneration of alveolar type 2 cells as well as hyperplasia, alveolar inflammation, and pulmonary fibrosis (3). Mouse models of HPS, including the mouse homologs of HPS1 (pale ear) and HPS2 (pearl), similarly display foamy degeneration of alveolar type 2 cells of adult animals.…”
mentioning
confidence: 99%
“…It possibly results from a defect in a protein required for the biogenesis, structure, or function of these various membrane-bound organelles. Idiopathic pulmonary fibrosis-like interstitial pneumonia has been known to be the most serious complication of HPS (7), and possible association of pulmonary inflammatory cell dysfunction, including alveolar macrophage, with the pathogenesis of interstitial pneumonia in HPS has been suggested (20,21). However, its detailed molecular pathogenesis remains unknown.…”
Section: Discussionmentioning
confidence: 99%